2010
DOI: 10.1093/ntr/ntq001
|View full text |Cite
|
Sign up to set email alerts
|

Preventing postpartum smoking relapse among diverse low-income women: A randomized clinical trial

Abstract: Introduction: Postpartum relapse rates are high among women who spontaneously quit smoking during pregnancy. This randomized clinical trial tested a Motivation and ProblemSolving (MAPS) treatment for reducing postpartum relapse among diverse low-income women who quit smoking during pregnancy (N = 251; 32% Black, 30% Latino, and 36% White; 55% <$30,000/year household income).Methods: Pregnant women were randomly assigned to MAPS/ MAPS+ or Usual Care (UC). Continuation ratio logit models were used to examine dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
91
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(95 citation statements)
references
References 70 publications
4
91
0
Order By: Relevance
“…The criteria for inclusion in the particular risk set were the following: five or more cigarettes per day in the three months before or in pregnancy for smoking; seven drinks per week or three or more per day during the six months prior to or in pregnancy for alcohol; any marijuana use during the six months prior to or in pregnancy for marijuana; or any cocaine use in the six months prior to or during pregnancy. The five cigarette minimum was based on the smoking literature in perinatal women (Cnattingius, 2004;McBride et al, 1992;Reitzel et al, 2010;Tong et al, 2008), and used the minimum amount, which allowed us to capture the majority of smokers. For alcohol the National Institute on Alcohol Abuse and Alcoholism definition for at risk drinking in women was used (National Institute on Alcohol Abuse and Alcoholism, 2014).…”
Section: Development Of Substance Use Risk Sets For Analysismentioning
confidence: 99%
“…The criteria for inclusion in the particular risk set were the following: five or more cigarettes per day in the three months before or in pregnancy for smoking; seven drinks per week or three or more per day during the six months prior to or in pregnancy for alcohol; any marijuana use during the six months prior to or in pregnancy for marijuana; or any cocaine use in the six months prior to or during pregnancy. The five cigarette minimum was based on the smoking literature in perinatal women (Cnattingius, 2004;McBride et al, 1992;Reitzel et al, 2010;Tong et al, 2008), and used the minimum amount, which allowed us to capture the majority of smokers. For alcohol the National Institute on Alcohol Abuse and Alcoholism definition for at risk drinking in women was used (National Institute on Alcohol Abuse and Alcoholism, 2014).…”
Section: Development Of Substance Use Risk Sets For Analysismentioning
confidence: 99%
“…Trait hostility consistently predicts higher smoking rates in both men and women (Lipkus et al, 1994;Siegler et al, 1992;Whiteman et al, 1997). In contrast to the large number of studies focusing on the association between maternal depression/ stress and smoking during pregnancy (Bullock et al, 2001;Businelle et al, 2010;Cinciripini et al, 2010;Ludman et al, 2000;Munafò et al, 2008;Reitzel et al, 2010), few investigated anger, hostility, or aggression among pregnant smokers. One exception is the study by Schuetze et al (2008), which indicated that pregnant smokers report higher hostile mood and maternal hostility.…”
mentioning
confidence: 99%
“…[40] In this pilot, 23% quit spontaneously after finding out they were pregnant, which was consistent with the literature. [23,38] Unfortunately, most spontaneous quitters return to smoking during postpartum. [16,23,26,41] The majority resume smoking within six months, [10,25] and this increases to as much as 80% within one year after delivery.…”
Section: Discussionmentioning
confidence: 99%
“…[23,38] Unfortunately, most spontaneous quitters return to smoking during postpartum. [16,23,26,41] The majority resume smoking within six months, [10,25] and this increases to as much as 80% within one year after delivery. [11] The rate of smoking relapse for low-income women is higher than all pregnant women.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation